2019
DOI: 10.29115/sp-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Online Respondents to Participate in Alternative Modes of Data Collection

Abstract: This study investigates online respondents' willingness to participate in research when using alternative data collection modes and techniques. The study compares mail surveys; face-to-face surveys; telephone interviews; and data collection techniques using apps, wearables, and register data. We also investigate whether respondents find certain topics relatively attractive to have measured in an alternative way compared to surveys. The results are based on a probabilitybased sample of about 2,000 Dutch respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 7 publications
(6 reference statements)
3
40
0
2
Order By: Relevance
“…Additionally, there is an apparent age bias in our study as 79% of respondents are in 30-44 years age group. This follows the universal trend of response in online surveys 33 where it has been shown that younger participants (up to 44 years) are more keen to take such online surveys as compared to those who are 45-54 years and older, who prefer other survey modalities such as mail (paper and pencil) survey.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, there is an apparent age bias in our study as 79% of respondents are in 30-44 years age group. This follows the universal trend of response in online surveys 33 where it has been shown that younger participants (up to 44 years) are more keen to take such online surveys as compared to those who are 45-54 years and older, who prefer other survey modalities such as mail (paper and pencil) survey.…”
Section: Discussionmentioning
confidence: 64%
“…Les difficultés démographiques associées aux questionnaires en ligne sont bien connues [36]. Une participation aux enquêtes en ligne diminue à partir de 50 ans [37] et une sur-représentation des femmes est souvent retrouvée, bien que les résultats soient hétérogènes concernant les études dans le domaine de la santé [38,39]. En outre, notre étude est subjective et aucune évaluation objective du temps du sommeil n'a été faite.…”
Section: Discussionunclassified
“…Moreover, since the analysis is based on one measurement point, the study allows no causal conclusions. Our study is also prone to limitations of online survey; results are based fully on self-reporting with the potential to reporting bias [61] and some groups (females, younger ages, higher educated), were over-represented in the survey sample compared to the general population [62, 63]. The survey on the other hand achieved satisfactory representation in terms of more than half of the Austrian provinces, migration background and employment status.…”
Section: Discussionmentioning
confidence: 99%